2013
DOI: 10.1098/rsif.2012.0838
|View full text |Cite
|
Sign up to set email alerts
|

Sticking like sticky tape: tree frogs use friction forces to enhance attachment on overhanging surfaces

Abstract: To live and clamber about in an arboreal habitat, tree frogs have evolved adhesive pads on their toes. In addition, they often have long and slender legs to facilitate not only long jumps, but also to bridge gaps between leaves when climbing. Both adhesive pads and long limbs are used in conjunction, as we will show in this study. Previous research has shown that tree frogs change from a crouched posture (where the limbs are close to the body) to a sprawled posture with extended limbs when clinging on to steep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 57 publications
3
100
0
1
Order By: Relevance
“…The term frictional adhesion has been coined to describe adhesion in geckos. It is unclear whether this term should also be applied to tree frog adhesion, but there is certainly A recent study by Endlein et al [26] has explained the frog's spreading behavior by studying the underlying ground reaction forces during this behavior. By using an array of multiple force transducers embedded in a walkway, the authors were able to record the ground reaction forces of a frog clinging on to the platform at varying slopes.…”
Section: Behavioral Strategies Of Adhering Frogsmentioning
confidence: 99%
“…The term frictional adhesion has been coined to describe adhesion in geckos. It is unclear whether this term should also be applied to tree frog adhesion, but there is certainly A recent study by Endlein et al [26] has explained the frog's spreading behavior by studying the underlying ground reaction forces during this behavior. By using an array of multiple force transducers embedded in a walkway, the authors were able to record the ground reaction forces of a frog clinging on to the platform at varying slopes.…”
Section: Behavioral Strategies Of Adhering Frogsmentioning
confidence: 99%
“…Using a finite element model, Peng et al [51] analyzed the change in the peel zone length and the peel force at different peel angles, Young's moduli, and spatula thicknesses. Endlein et al found that the adhesion forces of tree frogs can also be explained by the peeling theory [57].…”
Section: Peeling Model Of Gecko Spatulaementioning
confidence: 99%
“…It is unclear whether this term should also be applied to tree frog adhesion, but there is certainly interplay between friction and adhesion forces in frog toe pads too. A recent study by Endlein et al [26] has explained the frog's spreading behavior by studying the underlying ground reaction forces during this behavior. By using an array of multiple force transducers embedded in a walkway, the authors were able to record the ground reaction forces of a frog clinging on to the platform at varying slopes.…”
Section: Behavioral Strategies Of Adhering Frogsmentioning
confidence: 99%